Investigation of the Relationship of Media Habits with Anxiety and Fear in Dentistry among People Aged 6 to 15 Years - Fatemeh Zarebidoki; zahra Bahrololoomi; Maryam Vafaee Shahi (Mashhad University of Medical Sciences, 2022)
Introduction: Nowadays, most children spend a lot of time on electronic media, which can cause anxiety-related disorders. The present study aimed to investigate the relationship of media habits with anxiety about and fear of dentistry in people aged 6 to 15 years.Materials and Methods: In this cross-sectional study, participants were selected from people referred to Shahid Sadoughi Dental School (Yazd, Iran) aged 6 to 15 years. To measure their anxiety and fear, the Modified Child Dental Anxiety Scale and the Children's Fear Survey Schedule-Dental Subscale questionnaires were used, respectively. Additionally, a questionnaire was designed to assess the duration of watching TV and playing with a computer, cell phone, or tablet. Finally, the SPSS software (version 17) was utilized to analyze the data.Results: From a total number of 120 participants with a mean age range of 9.31±2.46 years, 39 were boys and 81 were girls. The results of the study pointed the relationship of anxiety and fear with the duration of watching TV and playing with a computer, tablet, or cell phone was not significant. However, there was a significant relationship between the duration of watching TV and the duration of playing with a computer, tablet, or cell phone in girls aged 10 to 15 years, mothers with associate degrees and above, as well as fathers with a diploma or associate degrees. Other findings were not significant.Conclusion: The results of the present study showed that media habits were not significantly associated with anxiety about and fear of dentistry in people aged 6 to 15 years.